Changed and Changing Gender and Family Roles and Domestic Violence in African Refugee Background Communities Post-Settlement in Perth, Australia. (July 2013) - Fisher, Colleen
In this study, domestic violence (DV) in five African refugee background communities post-settlement in Perth, Australia, is investigated—specifically, the interrelationship between experiences of DV, and changed and changing gender and family roles and responsibilities. The participatory qualitative design utilized in-depth interviews with 54 members of the Somalian, Sierra Leonean, Ethiopian, Liberian and Sudanese Communities, and focus groups with 24 professionals who support them. Three key dimensions of this interrelationship are discussed: "male loss of the breadwinner role and status, " "financial independence, " and "mismatch between formal response and expectations." The importance of understanding experiences of DV within the context of cultural transition is highlighted here.